High-voltage electrophoretic deposition of preferentially oriented films from multiferroic YMn2O5 nanopowders - Brankovic, G.; Brankovic, Z.; Sequinel, T. [UNESP]; Zunic, M. [UNESP]; Vukovic, M.; Tasic, N.; Marinkovic, B. A.; Cilence, M. [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier, 2013)
Processing of the YMn2O5 powder is very challenging, since it decomposes to YMnO3 and Mn3O4 at temperatures close to 1180 °C, while samples consolidation commonly demands high temperatures. The main goal of this work is to investigate a possibility to prepare thick films of YMn2O5, since their deposition generally requires significantly lower temperatures. Multiferroic YMn 2O5 was synthesized by the hydrothermal method from Y(CH3COO)3·xH2O, Mn(CH 3COO)2·4H2O and KMnO4 precursors. XRD, FE-SEM and TEM analysis showed that the obtained powder was monophasic, with orthorhombic crystal structure and columnar particle shape with mean diameter and length of around 20 and 50 nm, respectively. The obtained powder was suspended in isopropyl alcohol with addition of appropriate binder and deflocculant. This suspension was used for electrophoretic deposition of YMn2O5 thick films under the high-voltage conditions and electric fields ranging from 250 to 2125 V/cm. The films obtained at 1000 V/cm and higher electric fields showed good adhesion, particle packing, homogeneity and very low porosity. It was shown that the deposition in extremely high electric fields (KC=2125 V/cm) can influence the crystal orientation of the films, resulting in formation of preferentially oriented films. © 2012 Elsevier Ltd and Techna Group S.r.l.
Keywords: Electrophoretic deposition; Multiferroic; Oriented films; YMn2O5; Deflocculants; Electrophoretic depositions; High electric fields; High temperature; High-voltages; Hydrothermal methods; Isopropyl alcohols; Low porosity; Mean diameter; Multiferroics; Nano powders; Orthorhombic crystal structures; Particle packings; Particle shape; TEM analysis; XRD; Electric fields; Electrophoresis; Manganese; Thick films; Vapor deposition; Deposition